Robinson crusoe - Defoe, Daniel (Penguin Books Harmondsworth, Middlesex, England, 1994)
Robinson Crusoe, set ashore on an island after a terrible storm at sea, is forced to make do with only a knife, some tobacco, and a pipe. He learns how to build a canoe, make bread, and endure endless solitude. That is, until, twenty-four years later, when he confronts another human being. This novel was first published in 1719.